PARADOX PEGADAIAN SEBAGAI LEMBAGA JAMINAN DALAM PEMBERIAN KUR KEPADA UMKM - Hidayat, Yusup (Jurnal Magister Ilmu Hukum: Hukum dan Kesejahteraan, 2024)
AbstractOverlapping functions of non-bank financial institutions can give rise to moral hazard which has the potential to disrupt the financial system. Regulations have regulated each financial institution according to its characteristics so that any deviation affects the stability and health of the financial institution. The research method used is normative juridical with a statutory regulatory approach. This type of research uses a descriptive analysis approach. The objection is to determine and analyze the shift in the procurement function in the financial system in Indonesia. The results show that there has been a shift in the function of the financial system in Indonesia, where one can see that pawnshops can distribute People's Business Credit (KUR) credit to MSMEs, which should be done by banks and microfinance institutions because pawnshops can only distribute credit with collateral for material rights. in the form of pledges and fiduciaries or those based on fees, not as an intermediary institution. Mandatory KUR is only aimed at bank financial institutions and non-bank institutions and does not include pawnshops, due to the holding of microfinance institutions where pawnshops as a subsidiary of BRI also market KUR products, but preferably under the mechanism of a pawn guarantee institution. Keywords: KUR, Pegadaian, Financial SystemAbstractTumpang tindih fungsi lembaga keuangan bank non-bank dapat menimbulkan moral hazard yang berpotensi menggangu sistem keuangan. Regulasi telah mengatur setiap lembaga keuangan sesuai dengan karakteristiknya sehingga setiap penyimpangan akan berpotensi pada kestabilan dan kesehatan lembaga keuangan tersebut. Metode penelitian yang digunakan adalah yuridis normative dengan pendekatan peraturan perundang-undangan. Jenis penelitian menggunakan pendekatan analisys deskriftif. Tujuan penelitian adalah untuk mengetahui dan menganalisas pergeseran fungsi pengadaian dalam sistem keuangan di Indonesia. Hasil penelitian menunjukan bahwa terjadinya pergeseran fungsi sistem keuangan di Indonesia dimana dapat dilihat salah satunya pegadaian dapat menyalurkan kredit Kredit Usaha Rakyat (KUR) kepada UMKM yang seharusnya dilakukan oleh perbankan maupun lembaga keuangan mikro, karena pada dasarnya pegadaian hanya dapat menyalurkan kredit dengan jaminan hak kebendaan berupa gadai dan fidusia maupun yang berdasarkan fee bukan sebagai lembaga intermediary. Mandatory KUR hanya ditujukan kepada lembaga keuangan bank dan lembaga non-bank dan tidak termasuk pegadaian, namun demikian karena adanya holdingisasi lembaga keuangan mikro dimana pegadadaian sebagai anak perusahaan BRI turut memasarkan produk KUR namun sebaiknya dalam mekanisme lembaga jaminan gadai.Kata Kunci: KUR, Pegadaian, Sistem Keuangan